Aberrations in Incentive Learning and Responding to Heroin in Male Rats After Adolescent or Adult Chronic Binge‐Like Alcohol Exposure - Galaj, Ewa; Barrera, Eddy; Morris, Debra; Ma, Yao‐Ying; Ranaldi, Robert (Alcoholism, clinical and experimental research, 2020)
Background and Purpose Binge drinking is a serious problem among adolescents and young adults despite its adverse consequences on the brain and behavior. One area that remains poorly understood concerns the impact of chronic intermittent ethanol (CIE) exposure on incentive learning. Methods Here, we examined the effects of CIE exposure during different developmental stages on conditioned approach and conditioned reward learning in rats experiencing acute or protracted withdrawal from alcohol. Two or 21 days after adolescent or adult CIE exposure, male rats were exposed to pairings of a light stimulus (CS) and food pellets for 3 consecutive daily sessions (30 CS‐food pellet pairings per session). This was followed by conditioned approach testing measuring responses (food trough head entries) to the CS‐only presentations and by conditioned reward testing measuring responses on a lever producing the CS and on another producing a tone. We then measured behavioral sensitization to repeated injections of heroin (2 mg/kg/d for 9 days). Results Adolescent and adult alcohol‐treated rats showed significantly impaired conditioned reward learning regardless of withdrawal period (acute or prolonged). We found no evidence of changes to conditioned approach learning after adolescent or adult exposure to CIE. Finally, in addition to producing long‐term impairments in incentive learning, CIE exposure enhanced locomotor activity in response to heroin and had no effect on behavioral sensitization to heroin regardless of age and withdrawal period. Conclusions Our work sets a framework for identifying CIE‐induced alterations in incentive learning and inducing susceptibility to subsequent opioid effects. The goal of this study was to investigate the effects of chronic binge‐like alcohol intake on incentive learning and on the subsequent response to heroin. We show that binge‐like alcohol intake in adolescent and adult rats later impairs the acquisition of reward‐related learning and enhances the behavioral effects of heroin. Thus, the long‐term consequences of chronic binge‐like alcohol intake may include alterations in incentive learning and increased propensity for the emergence of drug abuse and addiction.